Isolation of Colour Components from Rubia tinctorum L.: Chromatographic Determination, Spectrophotometric Investigation, Dyeing Properties and Antimicrobial Activity - Golcu, Aysegul; Gitmisoglu, Demet; Dolaz, Mustafa; Serin, Selahattin (Asian Journal of Chemistry, 2010)
In this paper, a sensitive quantification high performance liquid chromatographic method for analysis of alizarin in madder root (Rubia tinctorum L.) obtained from South of Anatolia,Turkey is reported. The alizarin is separated on Zorbax SB C18 column with a water-acetonitrile gradient as eluent and measured with UV detection at 250 nm. With this method the aglycone alizarin can be analyzed. Regression equation that obtained from the calibration curve, revealed a linear relationship (r2 = 0.9981) between the mass of alizarin injected and the peak area. After, the colour components responsible for dyeing were determinated and its chemical constituents were established based on chemical and spectroscopic investigations. Afterwards, the wool fabrics have been dyed with combined mordanting and mordantless techniques. Fastness to light, washing and rubbing of the dyed fabrics were measured and discussed. Additionally, extracts (ethanolic and aqueous) of R. tinctorum L. root and dyed materials were investigated for their antimicrobial activities against eight pathogens (Aeromanas hydrophila, Bacillus megaterium, Corynebacterium xenosis, Pseudomonas aeruginosa, Micrococcus luteus, Enterococcus faecalis, Stapylococcus aureus and Escherichia coli). The extracts and dyed materials were not effective against the growth of Escherichia coli. The fabric dyed, however, showed less antimicrobial activity, as uptake of this dye in textile material is below minimum inhibitory concentration (MIC).